Nervous Shock, Tort and Accident Compensation: Tort Regained? - McLay, Geoff (Victoria University of Wellington Law Review, 1999)
This case note examines the recent Court of Appeal decision in Palmer v Danes Shotover Rafts dealing with the relationship between the common law and the Accident Compensation regime. The author acknowledges the practical importance of the Court’s holding in Danes Shotover Rafts that plaintiffs who have not suffered physical injury can sue for nervous shock. The author contends that the case is, like the exemplary damages cases, yet another example of the complex interaction between common law and statutory compensation regimes. The author argues that the case may signal a judicial switch from a welfare or communitarian approach to the interpretation of the Accident Compensation scheme to a rights based approach and that gives primacy to common law rights rather than to the integrity of the Accident Compensation scheme. A wider view not based solely on the statutory provisions, or on the assumption that the common law or statutory compensation regimes "trump" one another, but one which views the interaction between the common law and statutory compensation schemes as dynamic, may lead to a greater understanding of the relationship between statutory tort reform and the common law.